Risk of lymph node metastasis in early gastric cancer for a Western population. Issue 5 (30th December 2022) - Watanabe, Akie; McKendry, Geoffrey J.; Yip, Lily; Donnellan, Fergal; Hamilton, Trevor D.
Abstract: Introduction: Endoscopic resection (ER) of early gastric cancer (EGC) is increasingly used in Eastern countries due to their low rates of lymph node metastasis (LNM); however, there is a paucity of evidence in Western countries. We investigated LNM and its effect on overall survival (OS) in Western patients with EGC. Methods: Patients diagnosed with T1 gastric cancer between 2000 and 2017 were retrospectively evaluated. Univariate Kaplan–Meier, multivariate logistic and Cox‐regression models were used to assess the associations between clinical characteristics, LNM, and OS. Results: Among 86 patients, median age was 68 years and 72% were male. Node positivity was 30%. Two percent of patients met the classical guidelines for ER and all were node‐negative, while 16% met expanded criteria of which 14% were node‐positive. T1b disease (odds ratio [OR] 41.2 [95% confidence interval [CI] 1.62–1048], p  = 0.02) and lymphovascular/perineural invasion (OR 18.0 [95% CI 2.41–134], p  = 0.01) were predictive of node positivity. The 5‐year OS for node‐negative and node‐positive patients was 84% and 53% ( p  = 0.004), respectively. Conclusions: The risk of LNM in Western patients with EGC is higher; therefore, generalizability of the expanded criteria for ER should be interpreted with caution.